Research on the impact of dual pilot projects for low-carbon and innovative cities on carbon emission efficiency - Deng, Guangyao; Wu, You; Qian, Jiao (Frontiers in Environmental Science, 2024)
IntroductionTo achieve higher levels of development in China, building an environmentally friendly, low-carbon economic system is crucial, and policymaking plays a key role in this. Low-carbon and innovative cities pilot were launched in 2010 and 2008, respectively, with the range of pilot cities continuing to expand to date. This study aimed to calculating carbon emission efficiency and exploration the impact of dual pilot low carbon cities and innovative cities on carbon emission efficiency.MethodsUsing a multi-period DID model, this study analyses data from 284 prefecture-level cities in China between 2006 and 2020. The Super-SBM model with undesired output is applied to calculate urban carbon emission efficiency.ResultsThe study performs a sequence of robustness tests; it is still found that the dual-pilot policy has a positive promotion effect on urban carbon emission efficiency. Heterogeneity analysis indicates that the effect of dual-pilot is more significant in the central and western regions, with notable differences observed regardless of city size. The impact mechanism analysis finds that the dual-pilot policy boosts the rate by enhancing green innovation in general. The synergy analysis found that the efficiency improvement effect of the dual-pilot on carbon emissions would be more significant than that of the single-pilot policy, indicating that the dual-pilot policy has a synergistic effect and is still significant two years after either the single-pilot or the dual-pilot.DiscussionThe findings indicate that the dual-pilot policy has a better capacity to reduce carbon emission and improve its efficiency, which can work to achieve green development. Nevertheless, the limitation is that it fails to reflect spatial differences, and the relevant research will be further strengthened.